Conservation And Enhanced Tylophorine Through In Vitro Propagation And Precursor Feeding In Tylophora Indica-An Endangered Medicinal Plant - KSHIPRA SONI; SUMIT SAHNI; M. Z. ABDIN; ALKA NARULA (International Journal of Pharma and Bio Sciences, 2015)
The aim of the present study was to enhance the level of tylophorine in Tylophora indica through micropropagation and precursor feeding. Leaf and nodal segments were inoculated on Murashige and Skoog medium supplemented with different combinations and concentrations of auxins and cytokinins to standardize the micropropagation protocol. Out of 48 concentrations tried, the best regeneration medium for node was MS+0.5mg/l Indole-3-acetic acid (IAA)+2mg/l Kinetin (Kn) and for leaf was MS+0.5mg/l IAA+1mg/l Benzyladenine (BA). 5.64-fold higher level of tylophorine was obtained in in vitro raised plant as compared to in vivo grown mother plant. Tyrosine, a precursor of tylophorine was supplemented in various concentrations for different time intervals. The highest tylophorine production was (27.71µg/g DW) obtained in presence of tyrosine (2mg/l) for 48 hrs. This level was 2.81-fold higher than control cultures and 5.87-fold higher than in in vivo grown plants. This optimized protocol can be utilized for commercial level production of tylophorine.